Isolation and characterization of plant-growth promoting bacteria from Irish potato rhizosphere in Nyandarua county, Kenya - Igiraneza, Patience; Juma, Patrick; Kavoo, Agnes; Turoop, Losenge (Plant Science Today, 2025)
Irish potato, rich in antioxidants and minerals, is an important food source but faces challenges due to yield losses and excessive use of agrochemicals. To address these challenges, biological controls methods are gaining attention as eco-friendly alternatives. The rhizosphere hosts a complex interplay of roots, microbiota and soil, making it a key focus for sustainable agricultural practices. This study aimed to identify and characterize rhizosphere bacteria from Irish potato roots in Nyandarua county, Kenya. Root samples were collected using purposive and zigzag methods. Bacterial isolates were characterized through 16S rRNA gene sequencing and biochemical tests. Twenty-seven bacterial isolates with diverse morphological traits of colonies, including creamy-white, white and pink colonies of varying shapes and sizes were identified. Biochemical tests demonstrated all isolates as catalase and oxidase producers, with 14 isolates producing indole acetic acid (IAA) and 13 isolates producing hydrogen cyanide (HCN). Five isolates KG02 (9), KG02 (1), KG02 (2), KG02 (5) and KLm02 (1) were closely related to Bacillus aerius, Paenibacillus xylanexedens, Alcaligenes faecalis and Providencia huashanensis with 100 % sequence identity to known sequences in the NCBI database. This study highlights the importance of microbial diversity in soil ecosystems and their potential applications in sustainable agriculture. Further greenhouse experiments are recommended to evaluate their antagonistic and growth-promoting effects on Irish potatoes.